Location decisions of non-bank financial foreign direct investment: Firm-level evidence from Europe - Ronald B. Davies; Neill Killeen (University College Dublin, UCD School of Economics, 2015)
The non-bank financial sector in the euro area has more than doubled in size over the last decade reflecting the substantial growth in shadow banking activities. However, a large proportion of the non-bank financial sector remains unmapped as granular balance sheet information is not available for almost half of the sector. Motivated by these data gaps and employing firm-level data, this paper examines the location decisions of newly incorporated foreign affiliates in the non-bank financial sector across 27 European countries over the period 2004 to 2012. The probability of a country being chosen as the location for a new foreign affiliate is found to be negatively associated with higher corporate tax rates and geographic distance but increases with the size and financial development of the host country. The financial regulatory regime in the host country and gravity related controls such as the home and host country sharing a common legal system, language, border and currency are also found to impact the likelihood of non-bank financial FDI.
Keywords: F23; F65; G23; G32; 330; foreign direct investment; financial sector; shadow banking; location decisions; conditional logit models